2012
DOI: 10.4067/s0717-95022012000200065
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Pattern of Facial Fractures in Different Countries of the World

Abstract: SUMMARY:The aim of the present study was to examine the changes in the pattern of maxillofacial fractures between developed and developing countries over two time periods; (1987-1999) and (2000-2007). A comprehensive search of the literature using PubMed was conducted for publications on maxillofacial injuries published during the last 20 years. Only 45 articles met the inclusion criteria and the full-texts of these articles were thoroughly examined. For each of the included studies, different parameters were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 55 publications
(74 reference statements)
6
21
0
1
Order By: Relevance
“…11,12 However, looking specifically to the part of mandible fracture, this study has a different prevalence of mandible condyle fracture (5% of cases) while other studies tend to show higher prevalence. 13 In Table 2, we showed that the most common prevalence site of maxillofacial fracture were difference among studies. Still, the mandible fracture dominated to be the most prevalence site of fracture, as in Brazil, Australia, Pakistan, Nigeria, India, Europe, and Bandung.…”
Section: Discussionmentioning
confidence: 87%
“…11,12 However, looking specifically to the part of mandible fracture, this study has a different prevalence of mandible condyle fracture (5% of cases) while other studies tend to show higher prevalence. 13 In Table 2, we showed that the most common prevalence site of maxillofacial fracture were difference among studies. Still, the mandible fracture dominated to be the most prevalence site of fracture, as in Brazil, Australia, Pakistan, Nigeria, India, Europe, and Bandung.…”
Section: Discussionmentioning
confidence: 87%
“…The reason for preponderance of mandible was due to its prominence, mobility and its selection as a target of intentional violence. [12][13][14] Low level of awareness among population to wear full face helmet (Indonesian National Standard with chin protection) does impact the number of maxillofacial injury at Indonesia especially in Bali. Diagnosing maxillofacial trauma in our hospital was standardized.…”
Section: Discussionmentioning
confidence: 99%
“…Common causes of maxillofacial injuries by trauma are road traffic accidents, falls, sports and industrial accidents, falls from heights, school and domestic accidents involving children, birth injuries, gunshots and bomb blasts [4,[13][14][15]. These can further be seen in table 3.…”
Section: Traumamentioning
confidence: 98%